Genetic landscape of APOE in human longevity revealed by high-throughput sequencing. (April 2016) - Ryu, Seungjin; Atzmon, Gil; Barzilai, Nir; Raghavachari, Nalini; Suh, Yousin
Highlights: Discovery of variants in APOE gene region by pooled target capture sequencing. Identification of longevity-associated variants in regulatory region of APOE gene. Validation of longevity association of APOE ε2 allele in Ashkenazi population. Association of longevity-associated allele with beneficial lipid profiles. Abstract: Apolipoprotein E ( APOE ) gene has been the most replicated longevity-associated gene in humans. Two common APOE alleles are either significantly depleted (ε4 allele) or enriched (ε2 allele) in long-lived individuals as compared to controls. We performed high-throughput sequencing analysis of exons and 2 kb proximal promoter of APOE in 450 centenarians and 500 controls of Ashkenazi Jewish decent. We found two common regulatory variants, rs405509 ( p = 0.006) and rs769449 ( p = 0.036), that were significantly depleted in centenarians. Genotyping analysis of rs7412 and rs429358 showed significant enrichment of ε2 allele ( p = 0.003) and ε2/ε3 genotype ( p = 0.005), and significant depletion of ε3/ε4 genotype ( p = 0.005) in centenarians. Our findings support the hypothesis that variants in both coding and regulatory regions of APOE may contribute to longevity in humans.